The Influence of Healthy Financial, Business, and Human Resource Competence toward the Performance of Cooperation Institution: A Study on the People Living in the Coastal Area in Makassar - Ruslan, Muhlis; Musa, Chalid Imran; Parawansa, Dian Anggraece (International Review of Management and Marketing, 2017)
This research was aimed at analyzing cooperative performance at coastal areas around Makassar. This research was an explanatory research. The populations are cooperative members in coastal areas in Makassar consisting of 715 people. The sample was determined using formula made by Slovin, i.e. n = N / (1 + N.â„®2), where e = 0.05 or 5%. The data were analyzed using SPSS software. The results show that healthy organization, financial, business, and human resources' competence simultaniously influence cooperative performance. Partially, the influence of healthy organizations on the cooperative performance is 0.256, healthy financial is 0,003, healthy business is 0.000, and human resources' competence is 0,000. Therefore, significance of healthy organization on cooperatives performance is 1.139. It shows that Ho is accepted, and it means no influence because T-table is 1.960. The influence of healthy financial on the cooperative performance is 2,979. Tt shows that Ho is rejected, and it means that there is an influence. The significance of healthy business on the cooperatives performance is 4,003. It shows that Ho is rejected so there is an influence. In addition, the significance of human resource competencies on the cooperatives institution performance is 6.792. It shows that Ho rejected or influential. Keywords: Cooperation Institution Performance, Cooperation, Coastal Area JEL Classifications: G1, G3